“Humanization through Metaphors” and Epistemic Implications of Bauman’s Conception of Adiaphorization - Tuleikytė, Julija (Problemos, 2016)
The paper analyses Zygmunt Bauman’s conception of adiaphorization. Bauman exposes the problem of adiaphorization in two ways: by providing definitions of adiaphorization as moral indifference, and by describing aspects of social reality that are manifestations of adiaphorization. Descriptions of adiaphorization especially characterize the fourth phase of Bauman’s writing, featured by the “liquid turn”, when Bauman engages with the method of “humanization through metaphors”. As a result, epistemic connotations can be noticed, and the new term “epistemic indifference” is helpful for bringing out their specificity. One of the obstacles here is Bauman’s Levinasian conception of morality. The essay tackles the question of whether Levinasian presumption of the pre-sociality of morality prevents an interpretation of adiaphorization as not only moral, but also epistemic indifference, and arrives at the conclusion that it doesn’t.